A report on study on prevalence and creating database of multi sclerosis Kathmandu. - Chandra, Ayush (2021)
Executive Summary: Multiple sclerosis (MS) is a chronic autoimmune, inflammatory neurological disease of the central nervous system (CNS MS attacks the myelinated axons in the CNS, destroying the myelin and the axons to varying degrees. This injury is mostly irreversible though varying in nature and medically it is called axonal loss (Black holes seen in MRI).At local level, this project will act as a stimulator for the health personal to always keep this disease as a differential diagnosis while seeing a patient with vague symptoms.This will help not only to the health workers but also to the patients as they will be benefited with the comparatively thorough physical exam. At national level, this will be of a tremendous help, as Nepal will have its own database that will be sustainable and firm on the disease that is labeled ignored disease till now. It will also help at an international level. The data of such an ethnically varied country will be internationally recognized. It will be a 'talk of the world'. the database of first 50 patients shall provide the basis for more accurate prevalence estimates and long-term monitoring of epidemiological trends of MS in Nepal. Second, the database will establish a study base for patient-centered MS research in Nepal, thereby focusing on assessments of the disease burden for persons with MS and their relatives and proxies. Along the same lines, the MS database aims to contribute research to previously understudied topics concerning patients' life circumstances and experiences, as well as on clinical and health care related aspects. Third, by creating a versatile database and a flexible study infrastructure, the registry will offer a platform for nested investigations. From the outset, its main aim is to be an interdisciplinary, open, collaborative project, designed to leverage other existing research efforts. In the study, informed consent documents include agreements to allow future data exchanges between the Nepal Health Research Council (NHRC) and the Nepal Ministry of Health and Population for data validation and research projects. This study will be bound to complete and setup database of 50 MS patients in given duration time of 4 months as provided by NHRC in contract.